Advanced nanomaterials for modulating Alzheimer's related amyloid aggregation. Issue 1 (12th December 2022) - Shao, Xu; Yan, Chaoren; Wang, Chao; Wang, Chaoli; Cao, Yue; Zhou, Yang; Guan, Ping; Hu, Xiaoling; Zhu, Wenlei; Ding, Shichao
Abstract : Based on the dimensional scale, this review summaries the use of nanomaterials in the modulation of amyloid aggregation. The effects include intermolecular interaction, chelation, photothermal effect, photocatalytic oxidation, and drug delivery. Abstract : Alzheimer's disease (AD) is a common neurodegenerative disease that brings about enormous economic pressure to families and society. Inhibiting abnormal aggregation of Aβ and accelerating the dissociation of aggregates is treated as an effective method to prevent and treat AD. Recently, nanomaterials have been applied in AD treatment due to their excellent physicochemical properties and drug activity. As a drug delivery platform or inhibitor, various excellent nanomaterials have exhibited potential in inhibiting Aβ fibrillation, disaggregating, and clearing mature amyloid plaques by enhancing the performance of drugs. This review comprehensively summarizes the advantages and disadvantages of nanomaterials in modulating amyloid aggregation and AD treatment. The design of various functional nanomaterials is discussed, and the strategies for improved properties toward AD treatment are analyzed. Finally, the challenges faced by nanomaterials with different dimensions in AD-related amyloid aggregate modulation are expounded, and the prospects of nanomaterials are proposed.